2021
DOI: 10.3390/jcm10020355
|View full text |Cite
|
Sign up to set email alerts
|

Laser Interstitial Thermal Therapy in Patients with Newly Diagnosed Glioblastoma: A Systematic Review

Abstract: Background: Laser interstitial thermal therapy (LITT) is a minimal invasive neurosurgical technique for the treatment of brain tumors. Results of LITT have been reported in a case series of patients with deep seated and/or recurrent glioblastoma or cerebral metastases. With this review we aim to summarize the currently available evidence regarding safety and effectiveness of LITT in patients with newly diagnosed glioblastoma (nGBM). Methods: A literature search was performed using electronic databases (PubMed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Hence, knowing which patients will benefit most from LITT and to what extent is obscure. 4 Several studies exemplify the inconsistency of the available data. For example, Beaumont et al, 19 showed that EOA >90% improved the survival of 9 patients with corpus callosum ndGBM while Di et al, 12 showed that an EOA >70% increased the PFS of 20 patients with ndGBM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, knowing which patients will benefit most from LITT and to what extent is obscure. 4 Several studies exemplify the inconsistency of the available data. For example, Beaumont et al, 19 showed that EOA >90% improved the survival of 9 patients with corpus callosum ndGBM while Di et al, 12 showed that an EOA >70% increased the PFS of 20 patients with ndGBM.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Although its use has increased over the past few decades and safety repeatedly demonstrated, its role in treating patients with newly diagnosed glioblastoma multiforme (ndGBM) is not fully established, mainly because of small sample-size studies and confounding parameters. 4,5…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…75,76 This approach is also known as laser interstitial thermal therapy, stereotactic laser ablation, and MRI-guided laser ablation. 75,76 A 2021 review of the literature for effectiveness of this approach in newly diagnosed glioblastoma was inconclusive and noted the need for more well-designed prospective studies to generate conclusions. 76 No studies for this device that specifically included pregnant women have been reported.…”
Section: Intraoperative Brachytherapy Devicementioning
confidence: 99%